2021
DOI: 10.1111/1365-2478.13077
|View full text |Cite
|
Sign up to set email alerts
|

2.5D geophysical model of the Gällivare mining area: An integrated study to model the top 4 km of the subsurface and guide for future exploration activities

Abstract: Potential field and Slingram data alongside rock physical properties, drill‐core information and results from geological field mapping were used to investigate the geometry of the geological structures in the Gällivare area in regional scale. The main purpose of this study was to delineate the vertical and lateral extension of the Malmberget felsic volcanic rocks, the Dundret and Vassaravaara units as well as geological structures related to the crustal‐scale Nautanen deformation zone. Furthermore, we aimed at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Second, the late orogenic magmatic rocks are regionally voluminous and outcrop extensively just outside of the Kiruna area (Figure 1). Tavakoli et al [103] recently showed potential field modeling results that indicate these intrusions have sheetlike geometries and it may be possible that similar sheetlike intrusions underly parts of the Kiruna area that are inaccessible to sampling. Faults and shear zones in the Kiruna mining district likely played an important role for the transport of fluids and heat, and recent work has shown that basin inversion during D 2 affected the district with many fault zones being reactivated, including the northern continuation of the shear zone hosting the Rakkurijärvi IOCG deposit [21].…”
Section: Energy Drive Insights For the Mineral Systemmentioning
confidence: 99%
“…Second, the late orogenic magmatic rocks are regionally voluminous and outcrop extensively just outside of the Kiruna area (Figure 1). Tavakoli et al [103] recently showed potential field modeling results that indicate these intrusions have sheetlike geometries and it may be possible that similar sheetlike intrusions underly parts of the Kiruna area that are inaccessible to sampling. Faults and shear zones in the Kiruna mining district likely played an important role for the transport of fluids and heat, and recent work has shown that basin inversion during D 2 affected the district with many fault zones being reactivated, including the northern continuation of the shear zone hosting the Rakkurijärvi IOCG deposit [21].…”
Section: Energy Drive Insights For the Mineral Systemmentioning
confidence: 99%